Semantic ambient media: From ambient advertising to ambient-assisted living - Pogorelc, B.; Vatavu, R.; Lugmayr, Artur; Stockleben, B.; Risse, T.; Kaario, J.; Lomonaco, E.; Gams, M. (2012)
The term ambient media was in its beginning used only for ambient advertising. Nowadays it denotes the media environment and the communication of information in ubiquitous and pervasive environments. With the addition of intelligence, the new field of semantic ambient media was established. In recent years, the field of semantic ambient media has spread its span from only a few sub-areas, such as ambient advertising, to new ones, such as ambient-assisted living (AAL) and health-monitoring media, significantly supported by intelligence. The study presented in this paper provides an advanced introduction to the field of semantic ambient media including the solutions for threat issues and illustration of success stories of the field. It conducts a survey of the related work and presents a thorough discussion of it. The related work is grouped according to the coverage of the principles of semantic ambient media. Based on the state-of-the-art research, the future possibilities of the field are demonstrated, especially for the ambient-assisted living, audio-visual rendering of media objects, user design principles and the society impact of the field. The paper provides ideas for impacting ambient media and directions and questions for further research. It also discusses the potential of the combination of several research studies. © 2010 Springer Science+Business Media, LLC.